2016
DOI: 10.3892/or.2016.4575
|View full text |Cite
|
Sign up to set email alerts
|

Enabling personalized cancer medicine decisions: The challenging pharmacological approach of PBPK models for nanomedicine and pharmacogenomics (Review)

Abstract: The existing tumor heterogeneity and the complexity of cancer cell biology critically demand powerful translational tools with which to support interdisciplinary efforts aiming to advance personalized cancer medicine decisions in drug development and clinical practice. The development of physiologically based pharmacokinetic (PBPK) models to predict the effects of drugs in the body facilitates the clinical translation of genomic knowledge and the implementation of in vivo pharmacology experience with pharmacog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 162 publications
0
15
0
Order By: Relevance
“…It has been suggested that as long as technological advancements empower the translational medicine capacity in enabling the pharmacological exploitation of cancer cell molecular and genomic knowledge, the advances to therapeutically overcome heterogeneity and to target the tumor cell microenvironment will occur at increasing rates [2][3][4][5][6][7][8][9][10]. A major milestone towards organelle-specific drug delivery was reached by the discovery of delocalized lipophilic cations (DLCs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that as long as technological advancements empower the translational medicine capacity in enabling the pharmacological exploitation of cancer cell molecular and genomic knowledge, the advances to therapeutically overcome heterogeneity and to target the tumor cell microenvironment will occur at increasing rates [2][3][4][5][6][7][8][9][10]. A major milestone towards organelle-specific drug delivery was reached by the discovery of delocalized lipophilic cations (DLCs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, PM approaches are continuously developed for chronic and complex diseases (i.e., cardiovascular, diabetes, arthritis, kidney disease) and mainly for cancer [60][61][62][63][64][65][66][67]. Their exploitation is continuously providing (i) advanced innovative tools in academia; (ii) data for the pharmaceutical industry to predict the most promising compound during R&D; and (iii) novel aspects in medical society as decision-making tools for optimum treatment response, which are applied in clinical practice [68,69]. It can be proposed that although EBP seems to oppose PM, they are actually mutually complementary both in their goals but also in their limitations [45,50].…”
Section: Clinical Pharmacology Therapeutic Drug Monitoring (Tdm) Special Population Groups and Pharmacogenetics/pharmacogenomicsmentioning
confidence: 99%
“…PBPK models have been utilized to predict dose and frequency of drug administration for cancer drugs [113,114]. These models, together with oncology and systems biology computation models for tumor growth and cancer progress, form a complex multiscale framework that is powerful in the development of anticancer agents [115].…”
Section: Model Parameterization For Special Populationsmentioning
confidence: 99%